2010
DOI: 10.4067/s0717-97072010000400008
|View full text |Cite
|
Sign up to set email alerts
|

Stress Degradation Studies of Ramipril by a Validated Stability-Indicating Liquid Chromatographic Method

Abstract: Ramipril is an angiotensin-converting enzyme inhibitor which has chemical structure susceptible to degradation, therefore in this work forced degradation studies of ramipril were carried out by a developed and validated stability-indicating liquid chromatographic method. Stress testing was performed on drug substance under hydrolysis (0.1 N HCl, water and 0.1 N NaOH), oxidation (3% H 2 O 2 ), heat (70ºC) and photolysis (UV and VIS radiation). The drug was degraded under acidic, neutral, alkaline, oxidation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The exact molecular weight may be obtained using this method for RMP before and after exposure to the heating stress induced by HME. As an example, as shown in Figure 3a, the mass spectrum of pure RMP was tested after thermal treatment at 100°C for two hours on a hotplate, considered to be similar to the HME The trace in the positive mode ionisation showed the presence of a peak with a molecular ion at m/z 399.2291 (elemental composition C 23 H 31 N 2 O 4 calculated with +/-0.7mDa accuracy, Figure 3b) matching the formula of the suggested RMP degradation product (RMP-DKP) (Angeli and Trezza, 2009;De diego et al, 2010;Hogan et al, 2000).…”
Section: Hplc and Lc-ms Analysis Of Rmp And Its Degradation Productmentioning
confidence: 91%
See 1 more Smart Citation
“…The exact molecular weight may be obtained using this method for RMP before and after exposure to the heating stress induced by HME. As an example, as shown in Figure 3a, the mass spectrum of pure RMP was tested after thermal treatment at 100°C for two hours on a hotplate, considered to be similar to the HME The trace in the positive mode ionisation showed the presence of a peak with a molecular ion at m/z 399.2291 (elemental composition C 23 H 31 N 2 O 4 calculated with +/-0.7mDa accuracy, Figure 3b) matching the formula of the suggested RMP degradation product (RMP-DKP) (Angeli and Trezza, 2009;De diego et al, 2010;Hogan et al, 2000).…”
Section: Hplc and Lc-ms Analysis Of Rmp And Its Degradation Productmentioning
confidence: 91%
“…In this work, we report, for the first time, the development of inline Raman spectroscopic analysis in combination with multivariate data analysis to monitor RMP drug content and RMP degradation product during HME processing. In the literature, several studies have shown RMP instability at different pH values, and under application of heat stress is ramipril-diketopiperazine (RMP-DKP) (De diego et al, 2010). Due to thermal sensitivity, RMP processing by HME represents a real challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Roca et al (2011) suggest that β-lactam antibiotics such as CFT will undergo thermal decomposition gradually at a temperature of 60°C-100°C following pseudo-firstorder kinetics. Meanwhile, at room temperature (23 ± 2°C), structurally, CFT is very stable for up to 4 days (De Diego et al, 2010). However, in the acid-base treatment, there were (hyperchromic and bathochromic) shifts in the peak of the CFT, which indicated that it was unstable (Figure 4).…”
Section: P R E S Smentioning
confidence: 99%
“…Partition coefficient (log p) of RMP is 3.41 and its pka is 3.17. RMP is a highly challenging compound which poses stability problems in acidic and alkaline media and it is sensitive to heat, moisture and mechanical stress [8][9][10] .…”
Section: This Is Anmentioning
confidence: 99%